Comparison of low cost 3D structured light scanners for face modeling - Bakirman, Tolga; Gumusay, Mustafa Umit; Reis, Hatice Catal; Selbesoglu, Mahmut Oguz; Yosmaoglu, Serra; Yaras, Mehmet Cem; Seker, Dursun Zafer; Bayram, Bulent (Optica Publishing Group, 2017)
This study aims to compare three different structured light scanner systems to generate accurate 3D human face models. Among these systems, the most dense and expensive one was denoted as the reference and the other two that were low cost and low resolution were compared according to the reference system. One female face and one male face were scanned with three light scanner systems. Point-cloud filtering, mesh generation, and hole-filling steps were carried out using a trial version of commercial software; moreover, the data evaluation process was realized using CloudCompare open-source software. Various filtering and mesh smoothing levels were applied on reference data to compare with other low-cost systems. Thus, the optimum reduction level of reference data was evaluated to continue further processes. The outcome of the presented study shows that low-cost structured light scanners have a great potential for 3D object modeling, including the human face. A considerable cheap structured light system has been used due to its capacity to obtain spatial and morphological information in the case study of 3D human face modeling. This study also discusses the benefits and accuracy of low-cost structured light systems. (C) 2017 Optical Society of America
Keywords: POINT CLOUDS; KINECT; REGISTRATION; RESOLUTION; ACCURACY; QUALITY; ROBUST; IMAGE; Optics